VENTRAL MEDIAN AND LATERAL FLANK APPROACH FOR OVARIOHYSTERECTOMY IN CAT - Bella Vera; Riki Siswandi; Raden Harry Soehartono (Jurnal Kedokteran Hewan, 2023)
This study was conducted to compare Ventral Median Approach (OHM) and Lateral Flank Approach (OHF) for feline ovariohysterectomy (OH). Fifteen healthy local female cats (Felis catus) with body weights ranged 2-4 kg and aged 1-2 years were divided into two groups, OHM (n= 8) and OHF (n= 7). Prior to OH, the cats were anesthethized using ketamine-xylazine and the sugery was performed by the same operator. The wound scoring showed a significantly higher difference in the OHM group on day 3 and 4 post-surgery. Scores of erythematous, swelling and dehiscence showed no significant differences. The 4Avet pain scale was significantly higher in OHF at the 2, 6, and 12-hours post surgery. The pain response was evaluated using baseline tactile Semmes-Weinstein Monofilaments and was significantly higher in OHF than OHM on day 1 to day 5 post surgery. Blood hematology, blood glucose and wound healing duration did not differ significantly between groups. The OHF approach showed greater post-operative pain than the OHM approach. Wound dehiscence was observed in two cats (25%) in OHM group from day 4 post-operative. The OHM approach showed a greater risk of complications than the OHF group and therefore requires better post-operative care. The OHF group showed a smaller risk of complications but requires better post-operative analgesic therapy.